Can a Woman’s Medical Tradition Flourish in the Midst of the Babylonian Talmud? - Kedar, Dorit (Women in Judaism)

(untitled) (Women in Judaism, Inc., 2022)
The Babylonian Talmud offers a very limited glimpse into women’s voices, words, and writings, and only seldom quotes them. In contrast, the woman Em is quoted by Abaye twenty-seven times, always in the context of medicine and always in an authoritative formula – “Em told me.” Abaye’s amra li Em (אמרה לי אם) opens a window into a unique healing tradition transmitted to the Talmud by a woman. This article will examine Em’s expertise through a gendered and cross-cultural prism. In addition, the article will explore Em’s substantial body of work in the medical field, and the similarities of some of her prescriptions to Greco-Roman healing techniques and to Mesopotamian magical practices.